A general model for store-carry-forward routing schemes with multicast in delay tolerant networks - Jiajia Liu; Xiaohong Jiang; Nishiyama, H.; Kato, N. (2011 6th International ICST Conference on Communications and Networking in China, 2011)
Delay tolerant networks (DTNs) are sparse and highly mobile wireless ad hoc networks, where no contemporaneous end-to-end path may ever exist at any given time instant, and thus the "store-carry-forward" kind of schemes becomes a natural routing option. A lot of models have been proposed to analyze the unicast performance of such routing schemes in the DTNs, while few works consider the multicast scenario. In this paper, we develop a general continuous time Markov chain-based theoretical framework to characterize the complicated message delivery process of the DTN multicast scenarios, based on which analytical expressions are further derived for both the expected delivery delay and expected delivery cost. The developed theoretical framework is general in the sense that: 1) it can be used to analyze the DTN multicast performance under the common "store-carry-forward" routing schemes; 2) it can also be used for the common mobility models; 3) it covers some available models developed for the DTN unicast as special cases. We then apply the theoretical framework to explore the delivery performance of two popular routing schemes, the epidemic routing and the two-hop relaying.